Mobile Ground Station for CubeSat Operations - Fexer, Sebastian; Hauer, Lars-Christian; Smolko, Alexander; Struß, Mark-Oliver; Solmaz, Pascal; Munzel, Tom-Malte; Thienel, Tom-Hendrik (2018)
Operators of CubeSats often use Amateur Radio frequencies to get remote access to their small satellites. The frequency bands used are VHF (144-146 MHz), UHF (430-440 MHz) and sometimes also S-Band (2400-2450 MHz). For TT&C and data downlink a ground station is required, special attention has to be drawn on costs and regular maintenance. The lifetime of these antennas and ground station components is usually < 5 years and the service for the complete setup binds manpower. Furthermore, Central European locations for ground stations are not the best choice for LEO satellites on a sun synchronous orbit. This leads to 3-4 overpasses per day, 2 overpasses with a high elevation which results in longer contact time and closer distance. Other locations like Inuvik (CAN) provide more than 12 overpasses per day; northern regions are very interesting for long and more frequent communication times between earth and LEO Satellites. Therefore, the Institute of Space Systems (DLR) in Bremen is developing a remote controlled and mobile ground station for amateur radio frequencies, including antennas, servers and modern transceivers.